BILATERAL ENTEROCOCCUS FAECALIS ENDOPHTHALMITIS WITH MULTIPLE RECURRENCES. Issue Volume 15:Issues 1(2021) (2021) - Aderman, Christopher M.; Chao, Daniel L.; Obeid, Anthony; Schwartz, Daniel M.; Bhisitkul, Robert B.; Chiu, Cynthia S.
Abstract : Purpose: To describe the first case report of a bilateral recurrent Enterococcus faecalis endophthalmitis postcataract surgery. Methods: Case report with a description of the timeline, diagnosis, and management of a patient with bilateral recurrent E. faecalis endophthalmitis. Results: An 89-year-old man presented 6 weeks' postcataract surgery with pain, tearing, and blurred vision in the left eye. B-scan ultrasonography revealed vitritis and cultures postvitrectomy grew E. faecalis . There was gradual improvement in vision postintravitreal vancomycin administration. Four years later, the patient experienced another episode of E. faecalis endophthalmitis in the right eye postcataract extraction, followed by several additional episodes in both eyes posttreatment. Conclusion: Enterococcus faecalis is a rare but highly virulent cause of endophthalmitis that may remain sequestered in the capsular bag, despite aggressive treatment. Even after recurrent episodes, early vitrectomy and aggressive antibiotic therapy may prove to be effective in preventing vision loss. Abstract : Enterococcus faecalis is a rare but highly virulent cause of endophthalmitis after cataract surgery. Here, we present the first reported case of bilateral recurrent E. faecalis endophthalmitis in a patient who underwent secondary intraocular lens placement in one eye, followed by cataract surgery in the other eye 4 years afterward.